KONTRAVENSI NILAI SOLIDARITAS DAN NILAI KUASA DALAM PEMENTASAN REOG PONOROGO - Suyudi, Muhammad (Ngabari: Jurnal Studi Islam dan Sosial, 2017)
This study aims to determine the controversy of the solidarity values and power values in the performance of the reog Ponorogo. The reog Ponorogo performance was classified into two: first, reog obyog or obyogan which was performed in the villages during the celebration event, the commemoration of the Republic of Indonesia Anniversary, the cleanup of the village and others. Secondly, the regency reog, its whose staging was arranged by the Department of Culture and Tourism of Ponorogo Regency, the performances included: (1) performing a full moon night, which was shown were delegates from the sub-district, and each sub-district had to prepare; (2) Festival of reog mini, for elementary and junior high school levels which are displayed on every anniversary of Ponorogo Regency; (3) National Reog Festival, which is held every Grebeg Suro event; and (4) Festival held once every two years before Grebeg Suro. This type of research is qualitative research using a phenomenological approach that describes data in accordance with existing phenomena. The technique of collecting data uses interview techniques and documentation. Data analysis technique uses data reduction, data display, and conclusion. The results obtained from this study are that the value of solidarity among members of the reog Ponorogo group is very high, it is proven that they are willing to sacrifice costs, time and energy for a good performance for the group. However, the Regional Government of Ponorogo Regency also has the power to regulate the performance of the Ponorogo regency. And sometimes this solidarity values and power values ??creates controversy even though the form of controversy is small.